Rancang Bangun Model Deteksi Ketinggian Obyek di bawah Jalur Komunikasi Line Of Sight (LoS) menggunakan Laser Distance Meter - narindra heronita wisha (Jurnal Jaringan Telekomunikasi, 2019)
The world of telecommunications is growing rapidly so that cellular operator providers are trying to upgrade their networks to meet the needs of their customers with good quality. One effort that can be done is to build a new Base Transceiver Station (BTS). The aim of this research is to create a detection tool capable of detecting objects at a certain height below the line of sight (LoS) line of communication using the laser technology that has been developed. Topographic surveys and building planning are very important and required before building a BTS with an LOS. In this study, the Laser distance meter (rangefinder model) can measure the farthest distance up to 135 meters due to the limited area used. Experiments were applied to several objects to test the ability of the laser used and obtained the maximum distance of the TS832 transmission media reaching 70.7 meters.